"Don't Put Words in My Mouth!" To what extent does socio-institutional accessibility create a divide amongst black, female practitioners within the South African Theatre industry? - Van Tonder, Hannah (My University, 2021)
The research seeks to critically engage with the power structures that have a circular flow within the South African Theatre Industry. The work seeks to highlight the dualism of age and accessibility and how this has created unequal power relations amongst black, female theatre practitioners. This research draws on two South African National Theatre Award Shows hosted annually in South Africa: the Naledi Theatre Awards hosted in Johannesburg and the Fleur Du Cap Awards hosted in Cape Town. The research interrogates how award-winning and award nominations bring societal validation and credibility that allows for personal reflection and socio-institutional accessibility to manifest.The aim is to find out whether black, female, theatre practitioners 'feel' the need to excavate these power relations for a different construct to be built; that asks for a shift in the subject to be at the forefront. The research seeks to reveal if the responsibility for change sits in the power and agency of the systemic structures that mediate theatre award spaces as well as the individuals that micro-manage these theatre spaces. This work focuses on Cape Town and Johannesburg based practitioners as these are the only two cities in which theatre awards, on a national level, currently take place. However, every province within South Africa has their own theatres and awards, including Durban, where the voices of Durban based practitioners are still a crucial part of the study. Who gets access to credibility within these socio-institutional spaces will help uncover who gets to speak and how they get to express themselves through such platforms. This work refuses to keep black women separate from the rest of the industry, but instead requests the platform for black women to stand on an even playing field alongside their counterparts when looking at systematic credibility
A research report submitted to the School of Social Sciences, Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirement for the degree of Master of Arts (by Coursework and Research Report), 2021